PENGARUH PENERAPAN PERMAINAN MAGIC BOX (KOTAK MISTERI) TERHADAP PERKEMBANGAN BAHASA ANAK USIA 5-6 TAHUN DI RA AL-FAJAR MEDAN DENAI - Laili Hajriah Simamora; Humaidah Br. Hasibuan; Zulfahmi Lubis (Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to determine: 1) the effect of the application of the game magic box on the language development of children aged 5-6 years; 2) the effect of the quiz / question and answer method on language development of children aged 5-6 years; 3) differences in the application of the game magic box with question and answer method for language development of children aged 5-6 years at RA Al-Fajar Medan Denai. The method used is quantitative research, the type of research is quasi experimental design using post-test design control group design (non equivalent control group design). The population is 26, namely 13 children of class B1 (experimental class) and 13 children of class B2 (control class). The results of this study are 1) The influence of the application of the game magic box on language development of children aged 5-6 years, seen from the calculated value = 10.2700> table = 2.064; 2) The influence of the question and answer method on the development the language of children aged 5-6 years, seen from the calculated value = 8.6782> table = 2.064; 3) There are differences in the influence of the application of the magic box (mystery box) with the quiz / question and answer method on the language development of children aged 5-6 years in RA Al-Fajar Medan Denai, seen from the calculated value = 2.7458 and table = 2.064.